ITS2 in calanoid copepods: reconstructing phylogenetic relationships and identifying a newly introduced species in the Mediterranean. Issue 1 (1st January 2017) - Sabia, L.; Di Capua, I.; Percopo, I.; Uttieri, M.; Amato, A.
Abstract: Phylogenetic inference and molecular taxonomy are becoming increasingly important approaches to classical morphological systematics and marine ecology. The number of molecular markers suitable for such goals is quite high, but general use restricts the list to a few of them, mainly mitochondrial (namely cytochrome c oxidase subunit I, COI and Cytochrome b), especially in copepods. The ribosomal cistronic regions have been widely used for broad phylogenetic analyses in different taxa. Among them, the internal transcribed spacers (ITS rDNA) are powerful tools for phylogenetic reconstructions at the different taxonomic levels, although not yet extensively used for copepods. In the present work, we tested the suitability of ITS2 rDNA marker to reconstruct the phylogenetic relationships of calanoid copepods using sequences retrieved from GenBank, complementing the phylogenetic positions of the species studied with their morphological and ecological traits. Through ITS2 rDNA we provided the first molecular evidence for the invasive calanoid Pseudodiaptomus marinus from the Mediterranean Sea (Lake Faro, Sicily, Italy), and compared it with the GenBank ITS2 sequences for P. marinus from Korea and other calanoid species. The divergence of the sequences of our P. marinus from those of Korean specimens was quite prominent (4.4%) and allowed us to hypothesise either a new forma living in the Mediterranean or a cryptic species. This study highlights the appropriateness of ITS2 for phylogenetic reconstructions and species identification, as well as for barcoding, meta-barcoding and phylogeographic approaches, and evidences the need for a more thorough knowledge of ribosomal regions in copepods from different sites.